Fostering Solidarity and Encouraging Shared Commitment: Chongqing Daily’s Narratives about the Front-line Workers and the Role of these Narratives in Containing Covid-19 - Li, Zou (European review (Chichester, England), 2021)
This article analyses Chongqing Daily’s narratives about the front-line workers during the pandemic outbreak and their role in containing the Covid-19. These narratives foreground the disruption of filial connections and family life of those on the front lines as well as the physical toll their work takes on the bodies of these workers. By highlighting the suffering of front-line workers through familiar experiences relating to the body and family connections, this article argues that these narratives enabled inter-subjective connections between the front-line workers and the rest of the population and, therefore, helped foster a feeling of solidarity among the population in controlling the virus. The descriptions about the practices of front-line workers in the quarantined areas and their social moral meaning also functioned as action models and explanatory frameworks for the public to rationalize and assign meaning to the behaviour required of them during the lockdown period, and thus encouraged a shared commitment to combating the virus. Thus, the Chongqing Daily narratives strengthened the social cohesion in Chongqing and helped unite the population for a total war against the pandemic.